Determinants of educational attainment in Egypt and MENA: a microeconometric approach - Badr, Menshawy (2012)
Using TIMSS data set on MENA countries, this study examines the determinants of educational outcome and gender inequality of learning in eight selected countries. The complicated structure of the data has been considered carefully during all the stages of the analysis employing plausible values and jackknife standard error technique to accommodate the measurement error of the dependant variable and the clustering of students in classes and schools. The education production functions provide broad evidence from mean and quantile analysis of very low returns to schooling; few school variables are significant and none have effects across countries and quantiles. In general, student characteristics were far more important than school factors in explaining test scores, but there was considerable variability across countries in which specific factors were significant. Strikingly, computer usage was found to influence students’ performance negatively in six MENA countries. Only Turkey and Iran had a significant positive effect of computer usage on maths achievements. Gender inequality of academic achievement has been investigated thoroughly using mean and quantile decomposition analysis. There is mixed picture of gender inequality across the eight countries with three pro-boys, three pro-girls and two gender-neutral. This exercise gives no general pattern of gender inequality across MENA. A detailed analysis of Egyptian students’ achievements explains the differential gap between school types, notably being single or mixed sex and Arabic or language schools. Single-sex schools perform better than mixed schools especially for girls. The single-sex language schools are more effective than the Arabic single sex school. This confirms the dominance of the language schools and is also related to the style and social-economic status of enrolled students.